2004
DOI: 10.1128/jcm.42.1.384-386.2004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Species in the Intestinal Mucosa of Patients with Ulcerative Colitis

Abstract: In a search for Helicobacter species in the intestinal mucosae of 42 patients with ulcerative colitis (UC) and 74 without UC, only H. pylori was found. Although the bacterium was detected in UC patients by culture (7.1%) and nested PCR (19.0%), its presence was not associated with the disease (P ‫؍‬ 0.13).Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) of unknown etiology that is confined to the large bowel mucosa. It seems to be a multifactorial disorder involving both genetic and environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 15 publications
(8 reference statements)
1
36
1
2
Order By: Relevance
“…may contribute to the persistence of colonic inflammation. This finding was in line with Oliveira et al [49] who demonstrated that only H. pylori was found in mucosal sample from patients with ulcerative colitis.…”
Section: Helicobactersupporting
confidence: 92%
“…may contribute to the persistence of colonic inflammation. This finding was in line with Oliveira et al [49] who demonstrated that only H. pylori was found in mucosal sample from patients with ulcerative colitis.…”
Section: Helicobactersupporting
confidence: 92%
“…In addition, a number of EHS including H. hepaticus and H. bilis have been shown to induce IBD-like disease in animal models utilizing immunodeficient animals. While initial reports found no evidence of EHS in IBD human patients Grehan et al 2004;Huijsdens et al 2004;Zhang et al 2011) in several subsequent studies EHS DNA, detected by PCR, Southern blot and fluorescent in situ hybridization, has been consistently found in a higher proportion of IBD patients compared to control patients (Bohr et al 2004;Oliveira et al 2004Oliveira et al , 2006Laharie et al 2009;Thomson et al 2011). In addition, there have been a number of reports of the findings of Helicobacteraceae DNA in children presenting with IBD (Zhang et al 2006;Man et al 2008;Kaakoush et al 2010).…”
Section: Enterohepatic Infectionsmentioning
confidence: 93%
“…Bacterial viability was assayed by checking motility by phase contrast microscopy. Mucus negative for H. heilmannii had a negative urease test, did not reveal any spiral bacteria in the smears and was PCR negative for the genus Helicobacter (28).…”
Section: Helicobacter Heilmannii Inoculummentioning
confidence: 99%